2019
DOI: 10.1037/cou0000318
|View full text |Cite
|
Sign up to set email alerts
|

An initial examination of the work as calling theory.

Abstract: Over the past decade, research on work as a calling has seen a rapid growth, with hundreds of empirical articles on the topic having been published. Until recently, however, there has been no comprehensive theoretical model of work as a calling to guide research. Duffy, Dik, Douglass, England, and Velez (2018) published the Work as Calling Theory (WCT), which provides a comprehensive model of the predictors and outcomes of living out a calling. The present study provides the first empirical examination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 57 publications
8
58
0
1
Order By: Relevance
“…Our results suggest that when employees enact their respective callings with high self-efficacy, they are more likely to be committed to their careers, and when they are able to enjoy greater autonomy at work, their commitments to their careers are strengthened and they thereby perform their tasks in a much more proactive way. These findings also support the argument addressed by Duffy et al (2019) and Rawat and Nadavulakere (2015) – that the mechanism of calling is complicated and, thus, personal and contextual factors are highly relevant.…”
Section: Discussionsupporting
confidence: 86%
“…Our results suggest that when employees enact their respective callings with high self-efficacy, they are more likely to be committed to their careers, and when they are able to enjoy greater autonomy at work, their commitments to their careers are strengthened and they thereby perform their tasks in a much more proactive way. These findings also support the argument addressed by Duffy et al (2019) and Rawat and Nadavulakere (2015) – that the mechanism of calling is complicated and, thus, personal and contextual factors are highly relevant.…”
Section: Discussionsupporting
confidence: 86%
“…In other words, employees who perceive a sense of calling and are given the chance to realize such a calling find it more meaningful and tend to be more engaged compared with those who are not able to find any congruence between their calling and the environment in which they are embedded in. These theoretical arguments, which are also empirically supported (i.e., Duffy, Douglass, Gensmer, England, & Kim, 2019), lead us to posit that perceiving a calling is positively and significantly related to intention to stay.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 73%
“…As a starting point, employees can be provided opportunities to discover their calling through guided exercises and activities facilitated by career counselors. Given the findings of Duffy, Douglass, Gensmer, England, and Kim (2019) on the role of work volition or privilege of choice in employment, it seems ideal to first determine perceived volition. This may be particularly important in developing countries such as the Philippines where job opportunities seem limited (Menguito, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could be suggested that in doing so they were living a temporarily unanswered calling and crafting their career by choosing public service (Berg et al 2010). As all eventually returned to the Church, it suggests that there is a possible gap in the theoretical model in Work as Calling Theory (WCT) whereby it does not account for the long-term pull of calling, even after it has stopped being lived (Duffy et al 2018(Duffy et al , 2019. This contributes to our understanding of calling within this context and is a worthwhile avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…As WCT is an emergent theory, there is as yet limited empirical research testing its propositions, although an initial study identified that the majority of its propositions are fully supported (Duffy et al 2019). Importantly, the perception of a calling has been found to directly predict living a calling through person-environment (P-E) fit, potentially important when considering a career in an institution such as the Church (Duffy et al 2019). This study brings the focus of calling research back to its religious origins, exploring its potential applicability to faith workers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%